PETROCHEMICAL AND THERMODYNAMIC EVIDENCE ON THE ORIGIN OF KIMBERLITES - Perchuk L.L.; Vaganov V.I. (My University, 1980)
The petrochemistry of kimberlites from Yakutia and Lesotho has been studied using a silicate melt model with the SiO2, CO2 and H2O derivatives as the main anions.A model has been developed, according to which the dissolution of H2O in an ultramafic melt results in orthosilicates (H2SiC 4 -2 , H3SiO 4 – , H4SiO4 etc.) rather than metasilicates, while the dissolution of CO2 produces additional hydrocarbonate complexes. It suggests that at high PCO 2 1 , and where the orthosilicic calcium salt clusters are likely to be present in the magma, the kimberlite melt can break down into carbonate and silicate liquids. Therefore, the composition of kimberlite magma will be determined by the H2O/CO2 ratio under the relatively constant fluid pressure. This can be seen from the distinct fluidrs trend in the H2O-CO2-SiO2 diagram for the Yakutia and Lesotho diamond-bearing kimberlites. The H2O/CO2 ratio changes with the liquidus temperature along this trend (Perchuk and Vaganov 1977) which suggests that liquid immiscibility predominates over the simple CO2 solubility in the melts of kimberlite composition. The well-known Boyd's diagrams for the equilibrium PT-conditions in peridotites have been applied along with new experimental data to natural Cpx and Opx, and the PT-parameters were correlated for peridotite inclusions in kimberlite pipes in Yakutia and Lesotho. The liquidus temperatures for the extrapolated area of these correlations gave depths (pressures) at which kimberlite magmas are formed (200–250 km).The hypothesis on SiO2 partitioning between the melt and the fluid was used to calculate the composition of dry initial kimberlite which characterised the average mantle composition: SiO2 — 45.12; TiO2 — 2.49; Al2O3 — 3.58; Cr2O3 — 0.12; FeO — 9.32; MnO — 0.16; CoO — 0.11; MgO — 23.47; CaO — 13.44; Na2O — 0.20; K2O — 1.12; P2O5 — 0.69; S — 0.18; sum — 100 wt.%. This kimberlite is close to wehrlite in composition.
Keywords: Liquidus Temperature; Calcium Salt; Metasilicates; High PCO21; Kimberlite Pipe